Analisis Kemampuan Guru dalam Mengembangkan Perencanaan Pembelajaran di SD IT An-Najah - Novita Sari Nasution; Miftahul Jannah; Novia Ramadani; Namira Sazkia; Safran Hasibuan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The teacher's ability to plan learning is a very vital aspect in achieving educational goals. This research aims to explore various aspects of teachers' abilities, including their understanding of the curriculum, diversity of learning strategies, and the use of information technology in the teaching process. The results of the analysis of teachers' abilities in managing learning planning can become a basis for further improvement and development. This research uses a qualitative approach to explore and analyze teachers' abilities in developing learning plans at SD IT An-Najah. The population of this study were all teachers who taught at SD IT An-Najah. The main research instruments are in-depth interviews and observation. Data analysis was carried out through data reduction, data display and verification stages. The research results show that there are challenges and potential for development at SD IT An-Najah. Even though the majority of teachers have a good understanding of the curriculum, it needs to be understood that the integration of information technology is a problem that needs to be overcome.